Simulation And Hardware Development Of PM Brushless Dc Motor Drives - Satar, Mohamad Nasrul Abdul (2011)

(untitled)
This thesis presents simulation and hardware implementation of a 3-phase PM brushless DC (BLDC) motor drive using 120-degree, six-step current commutation control technique. The microcontroller used is PIC16F877 which functions to perform current commutation sequence, rotating direction control, speed control and reading Hall sensor signals. This microcontroller is a common and low-cost 40-pin MCU. The sensored type of controlling technique has been chosen in order to make this design suitable for both low speed and high speed applications plus control simplicity.